Pharmacoeconomic study of various treatment options for superficial vein thrombophlebitis of lower extremities - R. E. Kalinin; I. A. Suchkov; M. M. Uporov; D. S. Titov; M. Yu. Klishchenko (IRBIS LLC, 2023)
Background. The superficial veins thrombophlebitis (SVT) of lower extremities treatment can include conservative therapy (pharmacotherapy), crossectomy and phlebectomy.  Objective: рharmacoeconomic evaluation of pharmacotherapy, crossectomy (in combination with pharmacotherapy) and phlebectomy (in combination with pharmacotherapy) in patients with SVT of lower extremities.  Material and methods. Pharmacoeconomic evaluation was carried out using cost-effectiveness analysis (CEA) by calculating the costeffectiveness ratio (CER). The relapse/progression of the disease within 3 months after the end of treatment, the dynamics of pain, psychological, physical, social factors and the visual analog scale (VAS) indicator were used as parameters of clinical effectiveness. To assess the reliability of the obtained results, a deterministic, multivariate sensitivity analysis was performed.  Results. Considering part of patients without progression and relapse within 3 months after the end of therapy as an indicator of clinical effectiveness, it was found that median CER for pharmacotherapy (22069,01) was significantly lower than for crossectomy (83353,91) and phlebectomy (95702,96) (p=0,000). Also median CER for crossectomy technique was significantly lower than for phlebectomy (p=0,003). The CER values for the dynamics of pain, psychological, physical, social factors and VAS indicators were significantly lower for pharmacologic treatment than for crossectomy and phlebectomy. There were no statistically significant differences between CER values for crossectomy and phlebectomy.  Conclusion. It was established that if there are no medical contraindications, it is economically feasible to carry out pharmacotherapy for SVT of lower extremities, which requires the lowest costs to achieve full recovery. The pharmacoeconomic efficiency of crossectomy and phlebectomy are comparable.